Outlook on the Indonesian parlimentary elections 2004 - Irman G. Lanti (2009)
Indonesia will be holding a series of general elections this year. The closest of which is the parlimentary election. While much attention has ben paid on the direct presidential election, the parliamentary election is at least equally important, since only major parties or coalition of parties would be able to nominate candidates for the presidential election. Historically, the Indonesian politics have been organized around political groupings known as the aliran, espeically in conditions of unimpeded political competition. The last election in 1999 marked a return of aliran politics after a long hiatus. The election this year will not bring a major change to the structure of the aliran politics. The major parties will still be those hat have strong aliran bases, either in the nationalist, modernist Muslim or traditional Muslim camps. Having said that, the election this year will see an interesting dynamism, particularly in the nationalist camp, where the Sukarnoist parties led by the PDI-P will face challenges from some Suhartoist parties. In the modernist and traditionalist aliran, the race will be more structured and simple. A heated struggle for the non-aliran votes will occur, especially within Golkar. In the near future, a struggle for power in Golkar will take place and will probably change the outlook of the election.